The influence of land use activities towards Mass Rapid Transit (MRT) feeder bus service ridership - Sunoto, Yakin Nur; Ponrahono, Zakiah; Ash’aari, Zulfa Hanan; Rosni, Nur Aulia; Rabe, Noor Suzilawati; Mat Shukri, Nur Shazreena; Wan Ghazali, Wan Noratikah Wahidah (Malaysian Institute of Planners, 2021)
The Mass Rapid Transit (MRT) feeder bus service is a complementary public transport service provided to encourage ridership of MRT rail services in Malaysia. In brief, this feeder bus service plays a role in connecting people to and from MRT stations. The objective of this study is to determine the passenger volume generated at each MRT feeder bus stop location in the study area, and relate it to surrounding land use activities. Using the rule of thumb in public transportation systems, 200 m and 400 m radial buffers were identified as catchment areas of the bus stops. The key finding from this study is the relationship between volume of passenger and land use activities. This study concludes that land use activities influence MRT ridership, and that the presence of shelters or waiting poles is important to encourage ingress or egress.